Value Assessment, Real World Evidence and Fundamental Measurement: Version 3.0 of the Minnesota Formulary Submission Guidelines - Paul C. Langley (University of Minnesota Libraries Publishing, 2020)
This latest version of the Minnesota guidelines is intended to reassert the application of the standards of normal science in formulary submissions for new and existing pharmaceutical products and devices. This represents a paradigm shift from the existing value assessment standards which are focused on imaginary or I-QALY modeling of lifetime claims. The proposed new paradigm rejects this as pseudoscience; a failure to recognize the standards of normal science, in particular a failure to recognize the constraints of fundamental measurement. As a result, current health technology assessment is dominated by value assessments that create claims that are neither credible, nor empirically evaluable or replicable. The fatal flaw is the failure to recognize that QALYS are an impossible mathematical construct (hence the term I-QALY). The proposed paradigm recognizes that if there are claims for product value then, regardless of whether the claim is for clinical impact, quality of life or resource utilization, all claims must be empirically evaluable. If not, then they should be rejected. The Minnesota guidelines propose a new evidence based approach to formulary assessment, together with ongoing disease area and therapeutic class reviews. The focus is on claims that are specific to target patient populations that are claims for specific attributes and are consistent with the axioms of fundamental measurement. Manufacturers are asked to support claims assessment through protocols detailing the evidence base for claims assessment, the timelines for those assessments and the process by which claims assessments are reported back to formulary committees. Value assessment leads naturally to value contracting, revisiting provisional prices as new information is discovered and delivered to the formulary committee.